HPB P54 General surgery telemedicine clinics: here to stay post-pandemic?. (7th December 2022) - Urbonas, Tomas; King, Emily; Pepes, Sophia; Ceresa, Carlo; Gordon-Weeks, Alex; Reddy, Srikanth
Abstract: Background: The telemedicine clinic in general surgery has become widespread since the onset of the COVID-19 pandemic and has remained so following relaxation of restrictions on conventional face-to-face appointments. However, there has been significant scepticism regarding its continued utility. In particular, there is a concern that patients cannot be adequately assessed and counselled for invasive procedures, which may result in high cancellation rates on the day of procedure. The aim of this study was to assess the cancellation rate on the day of surgery for procedures booked in telemedicine clinics. Methods: We conducted a retrospective analysis of surgical procedures booked via hepatopancreatobiliary (HPB) and general surgery telemedicine clinics from March 2020 to November 2021. From September 2020 onwards, telemedicine clinics were only run for laparoscopic cholecystectomies for benign gallbladder disease. The primary outcome was the cancellation rate of surgical cases booked from telemedicine clinics. Statistical analysis was done using JASP 0.16.2 software. Results: We identified 240 cases booked for surgery from telemedicine clinic. 162 patients (68%) were female; the median age of the study population was 51 (16–81). 186 (78%) patients had gallstones, 19 (8%) gallbladder polyps, 13 (5%) secondary liver tumour, 5 (2%) liver cyst, 5 (2%) pancreatic tumour, 4 (1.7%) primary liver tumour, 2 (0.8%) gallbladder tumour and 6 (2.5%) other pathologies. 225 patients (94%) underwent surgery on their first admission. Procedures included 192 cholecystectomies, 10 open segmental liver resections, 6 laparoscopic segmental liver resections, 4 distal pancreatectomies, 3 open right hepatectomies, 2 Whipple procedures, 2 laparoscopic deroofing of the liver cyst, 2 laparoscopic lymph node biopsy, 1 extended right hepatectomy, 1 left hepatectomy, 1 small bowel resection and 1 exploratory laparotomy. 15 (6%) patients had surgery cancelled on the day of surgery, 14 of those were for laparoscopic cholecystectomy, 1 for laparoscopic liver resection. Only one such cancellation was deemed avoidable as it may have been prevented by a face-to-face assessment. The majority 212 (88%) of patients were ASA class 1–2; only 28 (12%) were ASA class 3. There was no significant association between high ASA (3) and cancellation rate (Chi square test 5% vs 14% p=0.062). Conclusions: Telemedicine clinic in general surgery was often the only option to assess and plan operative management for newly referred patients during the COVID-19 pandemic. Our series showed that it was feasible to assess and counsel patients on the phone even for major HPB procedures with a minimal cancellation rate on the day of operation.